Stress evaluation in thin films: Micro-focus synchrotron X-ray diffraction combined with focused ion beam patterning for d(o) evaluation - Baimpas, N; Le Bourhis, E; Eve, S; Thiaudiere, D; Hardie, C; Korsunsky, A (2013)
Nanocrystalline metallic coatings of sub-micron thickness are widely used in modern microelectronic applications. In X-ray diffraction experiments to determine both the residual and applied stresses in nanocrystalline coatings, one difficult challenge that comes up invariably is the determination of the strain-free lattice spacing d. The present study addresses this challenge by using the focused ion beam (FIB) to generate a built-in strain-free reference by patterning (milling) a 50 × 50 μm region of the coating to produce an array of small stress-relieved "islands" ~ 0.8 × 0.8 μm each. Transmission X-ray diffraction setup was used for data collection at DIFFABS beamline (Synchrotron SOLEIL, France). A 150 nm-thick multi-layered W-Cu nano-composite thin film on polyimide (Kapton®) substrate was studied. The samples were loaded incrementally using a compact uniaxial loading device, and micro-beam diffraction data were collected on and away from the reference array. It was shown experimentally that the "island" array remained approximately strain free throughout the experiment, providing an on-board d lattice spacing reference. The changing lattice spacing d in the coating was also monitored away from the array, to deduce the elastic strain evolution during deformation. The results and their implications are presented and discussed. © 2013 Elsevier B.V. All rights reserved.